Економічна сутність прибутку комерційного банку та джерела його формування - Іванова, В.О.; Кантур, С.Ф. (Культура народов Причерноморья, 2013)
У статті розглядаються сучасні трактування поняття «прибуток комерційного банку». На основі визначення сутнісних характеристик прибутку банку пропонується авторський підхід щодо його визначення. Розкривається значення прибутку та його види, а також досліджуються основні джерела формування прибутку за основними видами діяльності комерційного банку. Ключові слова: прибуток комерційного банку, джерела формування прибутку банку, чистий процентний дохід, чистий комісійний дохід, витрати банку. В статье рассматриваются современные трактовки понятия «прибыль коммерческого банка». На основе определения сущностных характеристик прибыли банка предлагается авторский подход к ее определению. Раскрывается значение прибыли и ее виды, а также исследуются основные источники формирования прибыли по основным видам деятельности коммерческого банка. Ключевые слова: прибыль коммерческого банка, источники формирования прибыли банка, чистый процентный доход, чистый комиссионный доход, расходы банка. The article considers the contemporary interpretations of the term “profit of the commercial bank”. Based on the determination of the essential characteristics of the bank's profit serves the author's approach to its definition. Reveals the value of profits and its species, and investigated the main sources of income for operating activities of the commercial banks. In today's profit and securing profitable business - a necessary factor of the existence of any business entity. The size of the profit depends addressing the major challenges facing the bank: an increase in the amount of own funds, replenishment of funds, the creation of general and special reserves, maintaining the image of the bank, financing of capital investments, the development of the branch network, the introduction of modern banking technologies, etc. Formation of the bank's profit is determined by the specifics of it as a business, range operations, and the current system of accounting and taxation. Profit as a valuable section tests the impact of various factors, that have regular and random. In this regard, management is especially important as the process of formation of profit eliminate the negative impact of these factors. At the same time preserving the quality of its earnings certainty suggests that this category can be considered as a managed object, which can be subjected to planning and forecasting, analysis and control. Keywords: profit of the commercial bank, the sources of income of the bank, net interest income, net commission income, expenses of the bank.